2003
DOI: 10.1111/j.1559-1816.2003.tb01924.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Breast Self‐Examination: A Test of the Information‐Motivation‐Behavioral Skills Model1

Abstract: The present research utilizes the information‐motivation‐behavioral skills (IMB) model (Fisher & Fisher, 1992, 2000) to predict breast self‐examination (BSE) and related behaviors in women. Results from a cross‐sectional survey study of 166 women found deficiencies in BSE‐related information, motivation, and behavioral skills, as well as insufficient rates of BSE‐related behaviors. Structural equation modeling indicated that IMB model variables account for significant variance in BSE and BSE‐related behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
65
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 44 publications
9
65
1
Order By: Relevance
“…Instead, motivation for the behavior is a necessary precursor for actual behavior change consistent with the information-motivation-behavioral skills model, in which knowledge and motivation both influence behavior (Fisher et al 1994;Fisher and Fisher 1992). More recent work found that knowledge does not consistently influence behavior (Misovich et al 2003) corroborated by other studies in a climate change context such as Kellstedt et al (2008) who find that climate change knowledge actually makes people less concerned and likely to act.…”
Section: Factors Affecting Stated and Actual Adoptionsupporting
confidence: 57%
“…Instead, motivation for the behavior is a necessary precursor for actual behavior change consistent with the information-motivation-behavioral skills model, in which knowledge and motivation both influence behavior (Fisher et al 1994;Fisher and Fisher 1992). More recent work found that knowledge does not consistently influence behavior (Misovich et al 2003) corroborated by other studies in a climate change context such as Kellstedt et al (2008) who find that climate change knowledge actually makes people less concerned and likely to act.…”
Section: Factors Affecting Stated and Actual Adoptionsupporting
confidence: 57%
“…Examples of its applicability include prediction of self-examination for breast cancer [44], risk-reduction behaviors related to HIV [40][41][42]45], or condom usage [46]. In most of these studies, the IMB Skills Model is used to predict actual behaviors whereas factors associated with other theories, such as the Theory of Planned Behavior [47][48][49] tend to focus on intentions.…”
Section: The Information-motivation Behavioral (Imb) Skills Modelmentioning
confidence: 99%
“…Using the IMB model, HIV and health promotion researchers have consistently found a strong association between motivation and behavioral skills (Misovich et al, 2003;Fisher et al, 1994;Fisher et al, 1999). Other studies have shown that behavioral skills mediate the effects of motivation on preventive behavior and HIV prevention behavior (Fisher et al, 1999;Avant et al, 2000;Bryan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other models such as the theory of reasoned action (Ajzen & Fishbein, 1980) and theory of planned reason (Ajzen, 1985;Ajzen & Fishbein, 2005), used in the study of HIV/AIDS and its risk factors, the IMB model has been validated extensively as providing a more comprehensive model for identifying socio-cognitive predictors of health behavior outcomes (such as HIV prevention) that are of theoretical and empirical importance (Carey et al, 1997;Fisher et al, 1996;Fisher & Fisher, 1992Fisher & Fisher, 1993;Fisher et al, 2003;Cargill et al, 2006). In addition, the IMB model has been applicable to behaviors outside the HIV domain including voting behavior (Glasford, 2008), breast self-examination behavior among women (Misovich et al, 2003), adolescence smoking behavior (Botvin el al., 1989) and oral rehydration behavior in developing countries (Foote et al, 1985). However, few studies have sought to test the applicability of prevailing theories of HIV risk behavior among students attending HBCUs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation